2007
DOI: 10.1530/rep-07-0328
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and the initiation of blastocyst implantation and decidualization

Abstract: The process of blastocyst implantation in mammals is remarkably variable, especially in the extent of trophoblast invasion of the endometrium. In most species studied, the earliest macroscopically identifiable sign of blastocyst implantation is an increase in endometrial vascular permeability in areas adjacent to the blastocysts. This is followed in species with invasive implantation by decidualization, again localized to areas adjacent to the blastocysts. In some species, the application of a stimulus to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
122
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 72 publications
5
122
0
Order By: Relevance
“…6 In the uterine stromal cells treated with estrogen plus progesterone, Hmgn1 could stimulate the expression of Cox-2 which was a rate-limiting enzyme in the biosynthesis of prostaglandins (PGs) and implicated in mouse decidualization. 25,26 Targeted disruption of Cox-2 led to defective decidualization. 25 Under artificially induced decidualization, Cox-2 inhibitor nimesulide diminished the production of uterine PGE 2 which was important for decidualization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In the uterine stromal cells treated with estrogen plus progesterone, Hmgn1 could stimulate the expression of Cox-2 which was a rate-limiting enzyme in the biosynthesis of prostaglandins (PGs) and implicated in mouse decidualization. 25,26 Targeted disruption of Cox-2 led to defective decidualization. 25 Under artificially induced decidualization, Cox-2 inhibitor nimesulide diminished the production of uterine PGE 2 which was important for decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…25 Under artificially induced decidualization, Cox-2 inhibitor nimesulide diminished the production of uterine PGE 2 which was important for decidualization. 26,27 mPGES-1 might catalyze the conversion of PGH 2 to PGE 2 and was also modulated by Hmgn1 during in vitro decidualization. 26 Cumulative evidences have declared that deficiency of Cox-2 or mPGES-1 caused a reduction in uterine Vegf mRNA level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, this step is followed by proliferation and differentiation of endometrial stromal cells into decidual cells, a process termed decidualization (reviewed by Kennedy et al 2007). In addition, the endometrium of rodents responds to non-specific stimuli with increased EVP and subsequent decidualization provided that the stimulus is applied at the appropriate time (Psychoyos 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in various species have shown that during pregnancy, the levels of prostaglandins (PGs) are elevated at implantation sites, suggesting a role of PGs in implantation (reviewed by Kennedy et al 2007). Moreover, numerous studies have shown that administration of inhibitors of PG synthesis and PG antagonists can inhibit or delay the initiation of implantation (reviewed by Kennedy et al 2007).…”
Section: Introductionmentioning
confidence: 99%